IMPLEMENTASI MOSES PADA PENCARIAN KATA TERJEMAHAN BAHASA INDONESIA-BATAK TOBA - Maria Asinta Marpaung; Viny Christanti Mawardi; Dali S.Naga (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Machine translation is the use a computer in translating text from one language to another. This application program is designed to search for words and sentences Indonesian to Toba Batak translation.  The purpose design of this application program is tointroducing vocabulary in the Indonesian-language Batak Toba based on Moses. Translated results is generated based on documents that has been created. This application is tested by the method of Black Box Testing, testing the truth table, and using BLEU. Based on the testing that has been done indicates all the functions contained in this application program has been running well. The system is designed to translate the Indonesian words and sentences to Toba Batak must related to the Bible and praise song lyrics. Documents are created for the search system of this translation is documents Indonesian and Toba Batak language of the Bible, the lyrics of the song of praise, and the combined documents Bible and praise song lyrics. The calculation of accuracy values obtained by each is different documents. Values obtained on documents greatest accuracy of song lyrics praise is 96.57%, compared with the Bible documents and combined these two documents is 79.84% and 80.28%.Keywords : Indonesian-Toba Batak, machine translation, Moses, Statistical Machine Translation